2022
DOI: 10.1093/icesjms/fsac196
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire and experimental surveys show that dolphins cause substantial losses to a gillnet fishery in the eastern Mediterranean Sea

Abstract: Common bottlenose dolphins (Tursiops truncatus) are known to depredate fishing gear, resulting in damage to the catch and/or the gear itself. The extent of this damage and estimated financial loss varies between areas, métiers, and survey methods. We quantified losses due to bottlenose dolphin depredation in a coastal gillnet fishery in the Thermaikos Gulf, Greece, in terms of CPUE reduction, catch damage, and gear damage. Experimental fishing effort was carried out over two seasons (2020 and 2021), along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Although hanging nets are the most often used fishing gear in the Greek SSF, there are few studies evaluating their environmental effect, with the majority of research focusing on the description of their catch profile and the assessment of their discards' ratio (e.g., Tzanatos et al, 2007). Villasante et al (2019) reported for the gillnet fishery of Thermaikos gulf (N. Aegean Sea), one of the most important fishing grounds for the Greek SSF, a particularly low discards ratio attributable to short soak-time employed by fishermen to avoid Mediterranean Marine Science Indexed in WoS (Web of Science, ISI Thomson) and SCOPUS The journal is available on line at http://www.medit-mar-sc.net www.hcmr.gr DOI: http://doi.org/10.12681/mms.31197 Short Communication competition with dolphins that heavily depredate their gear (e.g., Garagouni et al, 2022). Even though shortened soak time is an effective mitigation approach for lowering the quantity of discarded biomass (Uhlmann & Broadhurst, 2015), it is not expected to lessen the impact of fishing gear on the benthic environment, particularly during the retrieval process.…”
Section: Introductionmentioning
confidence: 99%
“…Although hanging nets are the most often used fishing gear in the Greek SSF, there are few studies evaluating their environmental effect, with the majority of research focusing on the description of their catch profile and the assessment of their discards' ratio (e.g., Tzanatos et al, 2007). Villasante et al (2019) reported for the gillnet fishery of Thermaikos gulf (N. Aegean Sea), one of the most important fishing grounds for the Greek SSF, a particularly low discards ratio attributable to short soak-time employed by fishermen to avoid Mediterranean Marine Science Indexed in WoS (Web of Science, ISI Thomson) and SCOPUS The journal is available on line at http://www.medit-mar-sc.net www.hcmr.gr DOI: http://doi.org/10.12681/mms.31197 Short Communication competition with dolphins that heavily depredate their gear (e.g., Garagouni et al, 2022). Even though shortened soak time is an effective mitigation approach for lowering the quantity of discarded biomass (Uhlmann & Broadhurst, 2015), it is not expected to lessen the impact of fishing gear on the benthic environment, particularly during the retrieval process.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that fishers in Crete experience approximately 36% losses in their total income, while those in the Ionian region experience a comparatively minor 1% reduction due to L. sceleratus impacts. The annual economic losses resulting from L. sceleratus depredation were comparable to those caused by marine mammals in Greek small-scale fisheries [50][51][52][53] (Supplementary Table S2). According to a previous study conducted in Crete in 2013, fishers had already identified L. sceleratus as the second most gear-damaging species after dolphins, followed by seals and turtles [15].…”
Section: Discussionmentioning
confidence: 99%
“…Despite their importance on regional and national levels, small-scale fishermen generate a very low profit margin, making them extremely vulnerable to challenges such as boat repairing, injuries, pandemics, economic crises and politics, reduced fish stocks and fishing grounds, climate change, non-native species and interactions with marine megafauna [ 51 ]. Therefore, even a small reduction in their profits, caused for instance by marine megafauna depredation, could have a significant negative economic impact on them [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%